Methods to Increase Microalgae Carbohydrates for Bioethanol Production - Ali, Esam Abu Baker; Idris, Muhammad; Irianto, Irianto; Zulkarnain, Muhammad; Alam, Syah; Amanah, Ayu; Firman, La Ode Muhammad; Mustika, Donny (Indonesian Journal of Computing, Engineering, and Design (IJoCED), 2022)
Compared to traditional lignocellulose biomass, microalgae contain little or no lignin. Traditionally, bioethanol production from microalgae undergoes three major steps: (i) pretreatment; (ii) polysaccharides hydrolysis into simple sugars; and (iii) sugar conversion into bioethanol by fermentation. Microalgae convert sunlight, water, and CO2 into algal biomass. Diatoms, green algae, bluegreen algae, and golden algae are four main classes of microalgae, whereas the two main species of algae are filamentous and phytoplankton algae. Microalgae convert solar energy efficiently, producing an enormous number of various metabolites. Many studies have been conducted to convert microalgae into various biofuels, such as biodiesel, bioethanol, biohydrogen, and biogas. However, compared to biodiesel, bioethanol production from algae throughfermentation consumes less energy with its simplified process. Considering these advantages, a number of potential applications for microalgae have been proposed and developed. Despite the promising of bioethanol from microalgae, it still has a number of obstacles, such as the low fermentable carbohydrate content of microalgae. This article intends to discuss the methods to increase microalgae carbohydrates thoroughly. To solve this problem, several nutritional starvations/limitations, like nitrogen and phosphorous starvation, are currently being considered in this paper.